Dramaturgia da carne: uma experiência na arte da performance - Schulz, Cláudia (2010)
This dissertation proposes a reflection on the fundaments and possible poetries observed in the web performance series Dramaturgy of Flesh, realized by the author from practical experimentations on the relation of the body with projected images (photography and videos) and its other possibilities. Three web performances compose this series; 4 Seminar of the Body Shopping List, Heart and Anatomical Map, all realized in the year of 2009. Dramaturgy of Flesh has been since its embryo a plural and multidisciplinary work which intends to wave and widen the perception of different artistic areas (performing arts and visual arts). It also dares to invade the field of anthropology and philosophy to emphasise even more this possible relation and fundament as an ephemeral art; that leaves its mark by the temporal suspension in the memory of each witness. The dramaturgy written in the body of this dissertation proposes to dissect some layers of the multidisciplinarity of the body in performance.